Charcoal-production, Air Pollutant Impacts on Ambient Environment and Associated Health Risks: A Systematic Review - Okimiji, Oluwaseun Princess (The Global Environmental Engineers, 2024)
Charcoal is a widely utilised fuel produced from the carbonisation of organic materials, such as wood and other biomass sources. Regrettably, airborne contaminants from traditional charcoal producing techniques can negatively impact human health and the environment. This research explore air pollutant emissions from traditional charcoal producing methods and their impacts on human health and the environment. This study utilised a qualitative synthesis methodology, incorporating case studies, archival research, and discourse analysis, to elucidate the impacts of charcoal production. The results demonstrate that the traditional charcoal production method results in substantial carbon loss from fuelwood and emits by-products of incomplete combustion, exacerbating serious health risks and degrading air quality associated with community health problems. Empirical evidence indicates that the majority of charcoal manufacturing workers lack awareness of the health risks associated with their working circumstances and the respiratory problems they face. Unsustainable environmental practices highlight the social and ecological repercussions of charcoal production. It is advisable to apply air pollution mitigation methods around charcoal kiln facilities to protect environmental and community health. The Environmental Protection Agency must actively implement effective oversight and integrated management to improve air quality and safeguard communities from air hazards. This study recommends testing high-efficiency technologies in communities capable of maintaining and assessing their effects on environmental degradation. Both governmental entities and humanitarian organisations should prioritise educational activities centred on effective land management approaches, as this study's findings suggest.